7,8-Dihydroxyflavone protects neurons against oxygen-glucose deprivation induced apoptosis and activates the TrkB/Akt pathway - Zhou,Qinxiang; Tang,Hao; Bai,Dingqun; Kong,Yuhan (PeerJ, 2022)
Background 7,8-dihydroxyflavone (7,8-DHF), a selective agonist of tropomyosin related kinase receptor B (TrkB), is known to exert protective effects in neurodegenerative diseases. However, the role of 7,8-DHF in TrkB signaling after ischemic stroke has remained elusive. Methods In the vitro model of ischemic stroke, we investigated the neuroprotective effect of 7,8-DHF through activation of TrkB signaling. Neurons subjected to oxygen and glucose deprivation/reperfusion were treated with the protein kinase inhibitor K252a and a knockdown of TrkB. Cell counting kit-8 (CCK-8) assay, Flow Cytometric Analysis (FACS), TdT-mediated dUTP nick end labeling (TUNEL) assay were conducted for measuring cell viability and numbers of apoptotic cells. And apoptosis-associated proteins were analyzed by Western blotting. Results Compared with the Control group, OGD/R group revealed lower cell viability by CCK-8 assay FACS and TUNEL assay showed increased rates of neuronal apoptosis. However, 7,8-DHF treatment increased cell viability and reduced neuronal apoptosis. Western blotting indicated upregulated Bax and cleaved caspase-3 and but downregulated Bcl-2 following OGD/R. Whereas 7,8-DHF treatment downregulated Bax and cleaved caspase-3 but upregulated Bcl-2. These changes were accompanied by a significant increase in the phosphorylation of TrkB and Akt following 7,8-DHF administration. However, the administration of K252a and knockdown of TrkB could alleviate those effects. Conclusion Our study demonstrates that activation of TrkB signaling by 7,8-DHF protects neurons against OGD/R injury via the TrkB/Akt pathway, which provides the evidence for the role of TrkB signaling in OGD-induced neuronal damage and may become a potential therapeutic target for ischemic stroke.
Keywords: 7,8-dihydroxyflavone; Tropomyosin related kinase receptor B; Akt; Oxygen and glucose deprivation/reperfusion; Apoptosis